Enhanced tissue regeneration through immunomodulation of angiogenesis and osteogenesis with a multifaceted nanohybrid modified bioactive scaffold - Hang Xue; Zhenhe Zhang; Ze Lin; Jin Su; Adriana C. Panayi; Yuan Xiong; Liangcong Hu; Yiqiang Hu; Lang Chen; Chenchen Yan; Xudong Xie; Yusheng Shi; et al. (Bioactive Materials, 2022)
Major traumatic tissue defects are common clinical problems often complicated by infection and local vascular dysfunction, processes which hinder the healing process. Although local application of growth factors or stem cells through various tissue engineering techniques are promising methods for the repair of tissue defects, limitations in their clinical application exist. Herein, we synthesized multifaceted nanohybrids composed of Quaternized chitosan (QCS), Graphene oxide (GO), and Polydopamine (PDA; QCS-GO-PDA). Covalent grafting of QCS and GO at a mass ratio of 5:1 (5QCS-1GO) displayed excellent biocompatibility and enhanced osteogenic ability, while addition of PDA (5QCS-1GO-PDA) reduced the level of reactive oxygen species (ROS). 5QCS-1GO-PDA was able to achieve wound tissue regeneration by reducing the inflammatory response and enhancing angiogenesis. Furthermore, Polylactic acid/hydroxyapatite (PLA/HA) composite scaffolds were printed using Selective Laser Sintering (SLS) and the hybrid nanomaterial (5QCS-1GO-PDA) was used to coat the PLA/HA scaffold (5QCS-1GO-PDA@PLA/HA) to be used for rapid bone regeneration. 5QCS-1GO-PDA not only improved angiogenesis and osteogenic differentiation, but also induced M2-type polarization of macrophages and promoted bone regeneration via the BMP2/BMPRs/Smads/Runx2 signaling pathway. The bidirectional enhanced healing ability of the multifaceted nanohybrids 5QCS-1GO-PDA provides a promising method of effectively treating tissue defects.